Rice SST Variation Shapes the Rhizosphere Bacterial Community, Conferring Tolerance to Salt Stress through Regulating Soil Metabolites - Tengxiang Lian (American Society for Microbiology, 2020)
ABSTRACT Some plant-specific resistance genes could affect rhizosphere microorganisms by regulating the release of root exudates. In a previous study, the SST (seedling salt tolerant) gene in rice (Oryza sativa) was identified, and loss of SST function resulted in better plant adaptation to salt stress. However, whether the rice SST variation could alleviate salt stress via regulating soil metabolites and microbiota in the rhizosphere is still unknown. Here, we used transgenic plants with SST edited in the Huanghuazhan (HHZ) and Zhonghua 11 (ZH11) cultivars by the CRISPR/Cas9 system and found that loss of SST function increased the accumulation of potassium and reduced the accumulation of sodium ions in rice plants. Using 16S rRNA gene amplicon high-throughput sequencing, we found that the mutant material shifted the rhizobacterial assembly under salt-free stress. Importantly, under salt stress, the sst, HHZcas, and ZH11cas plants significantly changed the assembly of the rhizobacteria. Furthermore, the rice SST gene also affected the soil metabolites, which were closely related to the dynamics of rhizosphere microbial communities, and we further determined the relationship between the rhizosphere microbiota and soil metabolites. Overall, our results show the effects of the rice SST gene on the response to salt stress associated with the soil microbiota and metabolites in the rhizosphere. This study reveals a helpful linkage among the rice SST gene, soil metabolites, and rhizobacterial community assembly and also provides a theoretical basis for improving crop adaptation through soil microbial management practices. IMPORTANCE Soil salinization is one of the major environmental stresses limiting crop productivity. Crops in agricultural ecosystems have developed various strategies to adapt to salt stress. We used rice mutant and CRISPR-edited lines to investigate the relationships among the Squamosa promoter Binding Protein box (SBP box) family gene (SST/OsSPL10), soil metabolites, and the rhizosphere bacterial community. We found that during salt stress, there are significant differences in the rhizosphere bacterial community and soil metabolites between the plants with the SST gene and those without it. Our findings provide a useful paradigm for revealing the roles of key genes of plants in shaping rhizosphere microbiomes and their relationships with soil metabolites and offer new insights into strategies to enhance rice tolerance to high salt levels from microbial and ecological perspectives.